2000
DOI: 10.1017/s0029665100000318
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of dietary intake in children

Abstract: When children and adolescents are the target population in dietary surveys many different respondent and observer considerations surface. The cognitive abilities required to self-report food intake include an adequately developed concept of time, a good memory and attention span, and a knowledge of the names of foods. From the age of 8 years there is a rapid increase in the ability of children to self-report food intake. However, while cognitive abilities should be fully developed by adolescence, issues of mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
596
6
27

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(639 citation statements)
references
References 83 publications
10
596
6
27
Order By: Relevance
“…The rates of misreporting in our study are similar to those reported in other studies in children using the same methodology [22,27]. The increasing bias towards under-reporting as children get older has often been described [41,42] and a number of reasons have been suggested such as eating behaviours and food patterns being less structures in adolescence [43], increased eating away from the home, particularly snacks, which are more likely to be forgotten. In addition, children in the 11-18-years-old age group are more likely to complete their own diet diary, whereas in the younger age group (4-10 years) dietary intake would usually be reported by a proxy person.…”
Section: Discussionsupporting
confidence: 88%
“…The rates of misreporting in our study are similar to those reported in other studies in children using the same methodology [22,27]. The increasing bias towards under-reporting as children get older has often been described [41,42] and a number of reasons have been suggested such as eating behaviours and food patterns being less structures in adolescence [43], increased eating away from the home, particularly snacks, which are more likely to be forgotten. In addition, children in the 11-18-years-old age group are more likely to complete their own diet diary, whereas in the younger age group (4-10 years) dietary intake would usually be reported by a proxy person.…”
Section: Discussionsupporting
confidence: 88%
“…For dietary assessments in the young, it has to be considered that the required cognitive abilities include an adequately developed concept of time, a good memory and attention span, as well as a knowledge of the food names. 28,29 However, by the age of 10 years, children can reliably report their food intake. 30,31 The increased availability of computers in schools and at home, the efficiency and economy (that is, standardization, savings in study personnel for interviewing, coding and data processing), as well as the attractiveness of computer software especially for adolescents makes it technically, financially and practically feasible to use self-administered computer-assisted tools for dietary assessments particularly in these age groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, outside of school, children have access to food from home, from friends' houses and from local shops and may eat substantial amounts of food in between meals (Davidson et al, 1986). These items may be more easily forgotten (Davidson et al, 1986;Poppitt et al, 1998;Livingstone & Robson, 2000;Novotny et al, 2001), or when they are remembered, the child may have difficulty recalling or estimating the number of servings consumed, especially if foods are shared with others or eaten directly from a larger packet (Thompson & Byers, 1994;Chambers et al, 2000). Such factors may have reduced both the validity and reliability of the data relating to the whole day compared to the data relating to morning break and lunchtime.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of dietary intake in RCTs with adult populations is often achieved using Food Frequency Questionnaires (FFQs) which assess normal intake of specific foods over particular time periods (eg see Thompson & Byers, 1994). However, these questionnaires can be unsuitable for use with children who tend to lack the cognitive skills needed to estimate 'normal' intake (Domel et al, 1994;Baranowski et al, 1997;Livingstone & Robson, 2000;McPherson et al, 2000). Asking parents to complete FFQs on behalf of school-aged children is also likely to result in imprecise measures of intake, partly because parents are not privy to their child's eating habits at school, and partly because parents do not necessarily observe the substantial amounts of snacking that children of this age engage in, both inside and outside the home (Davidson et al, 1986;Byers et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation